The Oxford handbook of business and the natural environment - Bansal, Pratima; Hoffman, Andrew J., 1961- (Oxford : Oxford University Press, 2012)
This handbook discusses the main issues, research, and theory on business and the natural environment, and how they impact on different business functions and disciplines.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Industrial management -- Environmental aspects -- Europe; Environmental responsibility -- Europe